Different reconstructive techniques for tumours of the distal tibia: intercalary resection, osteoarticular graft, or ankle arthrodesis?. (7th November 2020) - Sambri, Andrea; Dalla Rosa, Mattia; Scorianz, Maurizio; Guido, Davide; Donati, Davide M.; Campanacci, Domenico A.; De Paolis, Massimiliano
Abstract : Aims: The aim of this study was to report the results of three forms of reconstruction for patients with a ditsl tibial bone tumour: an intercalary resection and reconstruction, an osteoarticular reconstruction, and arthrodesis of the ankle. Methods: A total of 73 patients with a median age of 19 years (interquartile range (IQR) 14 to 36) were included in this retrospective, multicentre study. Results: Reconstructions included intercalary resection in 17 patients, osteoarticular reconstruction in 11, and ankle arthrodesis in 45. The median follow-up was 77 months (IQR 35 to 130). Local recurrence occurred in eight patients after a median of 14 months (IQR 9 to 36), without a correlation with adequacy of margins or reconstructive technique. Major complications included fracture of the graft in ten patients, nonunion of the proximal osteotomy in seven, and infection in five. In the osteoarticular group, three of 11 patients developed radiological evidence of severe osteoarthritis, but only one was symptomatic and required conversion to ankle arthrodesis. Functional evaluation showed higher values of the Musculoskeletal Tumour Society (MSTS) and American Orthopaedic Foot and Ankle Society (AOFAS) scores in the intercalary group compared with the others. Conclusion: Preservation of the epiphysis in patients with a distal tibial bone tumour is a safe and effective form of limb-sparing treatment. It requires rigorous preoperative planning after accurate analysis of the imaging. When joint-sparing resection is not indicated, ankle arthrodesis, either isolated tibiotalar or combined tibiotalar and subtalar arthrodesis, should be preferred over osteoarticular reconstruction. Cite this article: Bone Joint J 2020;102-B(11):1567–1573.